A Case Study of Stock Market Bubbles in the Indian Stock Market - Kanojia, Sunaina; Malhotra, Deepali (Indian Journal of Finance, 2021)
This paper’s objective was to analyze various stock market crashes to identify the stocks that offered a durable competitive advantage. To do so, stock market data were analyzed from January 2001 â€“ December 2018, and it was found that Nifty observed 10 major crashes during this period. After identifying the stocks that outperformed or performed moderately during the crisis, the compounded annual growth rate (CAGR) was computed for them. The results exhibited that the stocks that survived the market crashes had high CAGR and were considered stocks with a durable competitive advantage (DCA). The results exhibited that in India, stocks with DCA belonged to consumer goods, pharma and healthcare, and financial services sector. The present paper underlined the sectors in the Indian market, which are relatively immune to economic downturns and provided a cushion of safety compared to their other sector equivalents. The paper presented indicators for investors to identify stocks with DCA.